Global modulation of gene expression and transcriptome size in aneuploid combinations of maize - Hua Yang; Vincent Brennan; Zhi Gao; Jian Liu; Frimpong Boadu; Jianlin Cheng; James A. Birchler (Proceedings of the National Academy of Sciences, 2025)
Genomic imbalance refers to the more severe phenotypic consequences of changing a single chromosome compared to changing the whole genomic set. Previous genomic imbalance studies in maize have identified gene expression modulation in aneuploids of single chromosome arms. Here, the modulation of gene expression in more complex aneuploids, e.g., monosomy of one chromosome arm and trisomy of another was examined to determine the extent that combination aneuploids were additive, multiplicative, or rebalanced in terms of their effect on gene expression. A series of genetic crosses was performed to produce one, two, and three copies of one arm with independent one, two, and three copies of the other arm in each of the three genotypes for the opposite arm. In total, 31 combinations were analyzed. By examining RNA modulation, we found that cis genes on varied chromosome arms are generally more dosage-compensated in aneuploid combinations than in single aneuploidy even though some showed a clear dosage effect. For genes on the unvaried chromosomes ( trans ), there is greater modulation in most of the aneuploidy combinations. Finally, 22 of the 31 combinations were found to have an altered transcriptome size, suggesting that extensive stoichiometric changes of genomic regions upset global messenger RNA (mRNA) transcription. Overall, these results have important implications for understanding the role of genomic stoichiometry for mechanisms of gene expression, the evolution of dosage-sensitive duplicated genes, the evolution of sex chromosomes, the rapid growth adaptation of aneuploid cancer cells, and the control of quantitative traits.